THE IMPACT OF MODERN TECHNOLOGIES AND DIGITAL MARKETING ON TOURISM - Dalaboyeva Shodiya (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the transformative role of modern technologies and digital marketing in the tourism industry. It explores how digital tools such as artificial intelligence, big data, virtual reality, and social media marketing enhance tourist experiences, streamline operations, and boost destination competitiveness. The study highlights key trends, challenges, and future prospects of technology-driven tourism.